Null steering based beamforming techniques - Leng, Shuang (2011)
Null steering techniques have been used extensively for interference suppression purposes in communications where the desired signal is weak compared with the interfering signals. In null steering algorithms, the weights of an antenna array are selected such that the directional pattern has nulls in particular directions. In this manner, undesirable interference, jamming signals, or noise can be reduced or completely eliminated. One of the pioneering null steering algorithms is Davies method. Using Davies method, the null positions can be tracked one after another without affecting other null positions. Because of its ability to steer independent nulls, the Davies method has been attracting considerable interest for use in adaptive array processing. The Davies method has been further developed by Ko, where a fast null steering algorithm was presented. Using this algorithm, the complex zeros of the array are adjusted individually in a cyclical manner to track individual interferences. The research work in this thesis focus on several novel developments based on the Davies method and the Ko's method. Since look direction constraint is not used in the Davies method as well as the Ko's method, they are of great advantage in scenarios where the desired signal is weak compared with the interferences. However, in the environment where the desired signal is stronger or not significantly weaker than the interferences, a deep null will be placed in the direction of interest resulting in desired signal loss. In this thesis, we first study and propose an adaptive beamformer derived from a constrained null steering design. With the new method, the null positions can be selectively tracked so that the interference signals can be rejected while the desired signal is picked up by the array. The main advantages of the new null steering beamformer are the simplicity, faster convergence rate and lower complexity.